Streptococcus mutans isolated from a 4‐year‐old girl diagnosed with infective endocarditis - Yoshio Kondo; Tomonori Hoshino; Midori Ogawa; Kiyoshi Hidaka; Tomoyuki Hasuwa; Hiroyuki Moriuchi; Taku Fujiwara (Wiley, 2019)
Abstract Objectives Infective endocarditis (IE) has an extremely high fatality rate. In this study, we isolated a strain of Streptococcus mutans, which we called HM, from the blood drawn from a 4‐year‐old girl diagnosed with IE. We aimed to fully type the HM strain and investigate its biological properties, including its virulence with respect to IE. Material and methods A 16S rRNA phylogenetic tree and glucosyltransferase gene sequences were used to type HM. Serotyping was performed using the Ouchterlony method. Morphological observations were made using phase contrast and electron microscopy. Fibrinogen adhesion and biofilm formation were investigated to examine the tissue colonization properties of HM, whereas its bodily origin was determined from its fingerprinting pattern. Results The isolated strain was S. mutans serotype e. However, its morphology was observed to be short chains, unlike that of the NCTC 10449 reference strain. Fibrinogen adhesion and biofilm formation were more apparent than in NCTC 10449. The fingerprinting pattern showed that HM came from the patient's saliva. Conclusions HM differs from NCTC 10449 in its higher fibrinogen affinity. HM was also found to be derived from the oral cavity. These results highlight the importance of good oral hygiene for the prevention of IE in children.